Response of grasshoppers to the agricultural mosaics of the Cape Floristic Region biodiversity hotspot in South Africa - Adu-Acheampong, Samuel (Stellenbosch : Stellenbosch University, 2016)
Thesis (PhDAgric)--Stellenbosch University, 2017.